2017
DOI: 10.4084/mjhid.2017.032
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Homing and Engraftment Defects of Human Hematopoietic Stem and Progenitor Cells

Abstract: Homing of hematopoietic stem cells (HSC) to their microenvironment niches in the bone marrow is a complex process with a critical role in repopulation of the bone marrow after transplantation. This active process allows for migration of HSC from peripheral blood and their successful anchoring in bone marrow before proliferation. The process of engraftment starts with the onset of proliferation and must, therefore, be functionally dissociated from the former process. In this overview, we analyze the characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 72 publications
(72 reference statements)
0
24
0
2
Order By: Relevance
“…Successful bone marrow engraftment requires HSPC homing to the bone marrow vasculature, trans-endothelial migration, and lodging to the bone marrow niche. Research over the past few decades has revealed proteins that play key roles in HSPC homing and engraftment including selectins, ICAM-1, VCAM-1 on the EC 53,54 , beta1 subfamily integrins, and CXCR4 on HSPCs 2,55,56 . However, the mechanisms involved in trans-endothelial migration of HSPCs were unclear since loss of function studies focusing on these proteins showed HSPC defects mainly in short-term homing or long-term engraftment processes.…”
Section: Discussionmentioning
confidence: 99%
“…Successful bone marrow engraftment requires HSPC homing to the bone marrow vasculature, trans-endothelial migration, and lodging to the bone marrow niche. Research over the past few decades has revealed proteins that play key roles in HSPC homing and engraftment including selectins, ICAM-1, VCAM-1 on the EC 53,54 , beta1 subfamily integrins, and CXCR4 on HSPCs 2,55,56 . However, the mechanisms involved in trans-endothelial migration of HSPCs were unclear since loss of function studies focusing on these proteins showed HSPC defects mainly in short-term homing or long-term engraftment processes.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells alone have been proposed to have beneficial effects in patients suffering a multitude of pathologies across body systems, including: the lungs, brain, musculoskeletal system, peripheral nervous system, skin, and the heart . Although some have reported that direct injection of these cells into the affected tissues can have beneficial therapeutic effects, the level of engraftment of the cells to the site of application typically ranges between only 1% and 10%, and has been proposed to be as low as 0.001% . As a result, the number of cells that are typically used in these therapies tend to be very large, ultimately creating the potential for carcinogenesis and other negative outcomes.…”
Section: The Delivery Of Biological Therapeutics Using Hydrogelsmentioning
confidence: 99%
“…A first step in this process is homing of infused intravenously HSPCs to BM followed by their lodging into hematopoietic niches and engraftment. The homing process is facilitated by chemoattractants secreted from BM in response to myeloablative conditioning [4][5][6]. A crucial role in this step plays an α-chemokine stromal derived factor-1 (SDF-1) secreted by BM cells that survived myeloablative treatment [5,7,8].…”
Section: Introductionmentioning
confidence: 99%